Bahasa Tolaki di Kalangan Anak Remaja Dalam Kehidupan Sehari-hari di Desa Totombe Jaya - Indriyani, Indriyani; Rahman, Hidayah; Sukur, La Ode (JURNAL KABANTI: Kerabat Antropologi, 2024)
This research aims to determine the influence and causes of the fading use of the Tolaki language among teenagers in Sampara District in Konawe Regency. The selection of informants in this research used purposive techniques. This research uses Bronislaw Malinowski's theory of Cultural Diffusion (1944). The data collection technique used in this research is field research techniques using observation and in-depth interviews. This research is qualitative research using ethnographic research methods. The results of this research show that: First, there are several things that make the teenagers there unable to speak Tolaki, namely because of several external and internal factors. The internal factor is the family. Meanwhile, external factors are school and playmates. Second, because of their childhood habits, most of them are not taught from childhood, which makes it difficult for them to know their own regional language. This means that the teenagers there no longer use the regional language Tolaki but use the common language Indonesian.